Creative Thinking Skills of Students on Enviromental Pollution Theory at Muhammadiyah School: Keterampilan Berpikir Kreatif Siswa Pada Materi Pencemaran Lingkungan di SMP Muhammadiyah - Nia Dwi Asivah Asivah; Fitria Eka Wulandari (Universitas Muhammadiyah Sidoarjo, 2020)
The research aimed to reveal creative thinking skills of students on environmental pollution theory at SMP Muhammadiyah 5 Ngoro. The research method used is a quantitative description. The population used was 35 class VIII students. The samples taken randomly in this study were 32 students who came from using counting the Slovin formula. The research instrument used was a creativity test. The test is a data collection techniques used in this research. The results of the creativity test were analyzed using the calculation of creative thinking criteria and described into 4 criteria: very creative, creative, supportive, and less creative. Based on the results of the analysis, it can be concluded that students at SMP Muhammadiyah 5 Ngoro have creative thinking skills at a enough creative level.